Structural and Mössbauer Spectral Studies of Nanosized Aluminum Doped Manganese Zinc Ferrites - R. L. Dhiman; S. P. Taneja; V. R. Reddy (Advances in Condensed Matter Physics)
Nanoparticles of aluminum-substituted manganese zinc ferrites, Mn1.05Zn0.05AlxFe1.9−xO4 with 0.4≤x≤1.0 were synthesized by solid-state reaction route and characterized by XRD, TEM, and Mössbauer spectroscopy measurements. The particle size is found to very from 46 to 28 nm with increase of aluminum ions concentration. The unit cell parameter “aO” is found to decrease linearly with aluminum ions concentration due to smaller ionic radius of aluminum. The cation distributions were estimated from X-ray diffraction intensities of various planes. The theoretical lattice parameter, bulk density, porosity, X-ray density, oxygen positional parameter, ionic radii, jump length, as well as bonds and edges lengths of the tetrahedral (A-) and octahedral (B-) sites were determined. Fe57 Mössbauer spectra recorded at room temperature were fitted with two sextets corresponding to Fe3+ ions at tetrahedral (A-) and octahedral (B-) sites. The magnetic hyperfine fields at A- and B-sites show a gradual decrease with increase of Al3+ ion concentration, which has been explained on the basis of supertransferred hyperfine field. The cation distribution obtained from X-ray intensities and Mössbauer data indicates a decrease in Fe3+(B)/Fe3+(A) ratio with increasing aluminum concentration thereby suggesting a decrease in ferrimagnetic behavior.